Functional validation of putative PIP-box promoters of Xanthomonas citri subsp. citri using GFP as a reporter - Amistá, Luana Cristina [UNESP]; Ferreira, Rafael Marini [UNESP]; Othonicar, Murilo Ferreira [UNESP]; Lima, Carlos Antonio Couto [UNESP]; de Mello Varani, Alessandro [UNESP]; Ferrasa, Adriano; Ferro, Maria Inês Tiraboschi [UNESP]; Ferro, Jesus Aparecido [UNESP] (Springer Nature, 2025)
Background: Plant-Inducible Promoter boxes (PIP-boxes) are conserved sequences found within the promoter regions of various genes in phytopathogenic bacteria, including the Gram-negative bacterium Xanthomonas citri subsp. citri (X. citri), the causative agent of citrus canker. These sequences are activated by host plant signals during infection, playing a critical role in regulating genes linked to pathogenicity and virulence, thereby facilitating plant-pathogen interactions. Methods and results: This study evaluated the functionality and expression strength of putative PIP-box sequences located upstream of the XAC0360, XAC0416, XAC2370, and XAC2922 genes in X. citri subsp. citri strain 306 (X. citri 306). Engineered strains of X. citri 306 were created with expression vectors containing a gfp reporter gene driven by each respective PIP-box sequence. GFP expression was assessed in planta through fluorescence microscopy and quantitative PCR (qPCR). Fluorescence microscopy showed that the PIP-box promoter of XAC0416 exhibited strong transcriptional activity, with significantly higher fluorescence intensity than the promoters of XAC0360, XAC2370, and XAC2922. This indicates that the XAC0416 PIP-box is particularly effective for driving GFP expression and may serve as a valuable tool for future gene expression studies. Furthermore, the lack of fluorescence in the wild-type X. citri strain confirms the specificity of the engineered expression system. Conclusions: This study demonstrates that the tested PIP-box sequences function as active promoters, each exhibiting distinct expression strengths. The strong activity of the XAC0416 PIP-box highlights its potential for applications in the study of specific genes in X. citri.
Keywords: Gene expression; Inducible promoters; Plant-pathogen interaction; Virulence